Understanding, interests and informed consent: a reply to Sreenivasan. Issue 4 (24th April 2014) - Bromwich, Danielle
Abstract : It is widely agreed that the view of informed consent found in the regulations and guidelines struggles to keep pace with the ever-advancing enterprise of human subjects research. Over the last 10 years, there have been serious attempts to rethink informed consent so that it conforms to our considered judgments about cases where we are confident valid consent has been given. These arguments are influenced by an argument from Gopal Sreenivasan, which apparently shows that a potential participant's consent to research participation can be perfectly valid even if she fails to understand the risk-benefit profile of the study. I argue that Sreenivasan's argument fails. The set of clinical trials that is supposed to be ethical in the face of this kind of ignorance is empty. However, I argue that his argument is nonetheless instructive in allowing us to identify three important but neglected areas for future conceptual research on informed consent. I close by arguing that research on these identified questions promises to yield a defensible view of consent, lessen the burden of ambiguity on researchers attempting to obtain consent to research participation, and facilitate socially valuable research.